Health behavior, mental health – responses of police trainees to occupational stress (Academic Journal of Internal Affairs, 2019)
Our country the average really young police trainees are really young, when they start their police studies. The second year of the law enforcement school brings an additional challenge: they are probational police officers and law enforcement students at the same time. In my research I examine the correlate of health behavior, mental health and occupational stress, that they go through during the second part of their studies.
Keywords: police trainees; health behavior; occupational stress; mental health